Master Settlement And Acquisition Agreement (MSAA) Dan Master Refinancing And Note Issuance Agreement (MRNIA) Dalam Perspektif Hukum Perdata (Suatu Tinjauan Singkat) - Hertanto, Ari Wahyudi (UI Scholars Hub, 2026)
Abstract